2007
DOI: 10.1196/annals.1395.045
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis and Protein Oxidation Products

Abstract: The presence of a chronic inflammatory state has also been widely documented in end-stage renal disease patients receiving maintenance hemodialysis (HD). It is commonly attributed to the constantly renewed activation of circulating neutrophils and monocytes following blood passage through dialysis circuits and subsequent generation of activated complement components due to contact of plasma with bioincompatible membranes and/or transfer of endotoxins from the dialyzate to the blood compartment. This conjunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Table 1 lists the most commonly utilized biomarkers in human and experimental models. The application of these biomarkers has now unequivocally demonstrated that acute kidney injury, chronic kidney disease, and end-stage renal disease are states of increased oxidative stress [60][61][62][63][64][65]. A more complete approach with potential promise is the utilization of multiple biomarkers from both oxidant-generating and antioxidant pathways to assess oxidative stress [60,66].…”
Section: Assessment Of Oxidative Stress-biomarker Pitfallsmentioning
confidence: 98%
“…Table 1 lists the most commonly utilized biomarkers in human and experimental models. The application of these biomarkers has now unequivocally demonstrated that acute kidney injury, chronic kidney disease, and end-stage renal disease are states of increased oxidative stress [60][61][62][63][64][65]. A more complete approach with potential promise is the utilization of multiple biomarkers from both oxidant-generating and antioxidant pathways to assess oxidative stress [60,66].…”
Section: Assessment Of Oxidative Stress-biomarker Pitfallsmentioning
confidence: 98%
“…Indices of oxidative damage, especially the products of lipid peroxidation, are widely used as markers of oxidative stress [27] . AOPPs are more recently described, have been intensely investigated and appear to be good markers of oxidative imbalance as they can be used as an indicator of lipid peroxidation and are more stable and easier to sample [28] . We hypothesized that increased levels of AOPP may reflect oxidative damage to proteins associated with the development of endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Dityrosine is formed by ROS, enzymatic reactions, ultraviolet irradiation and lipid peroxidation [10,11,14,16]. AOPP are defined as dityrosine-containing cross-linked protein products and are considered to be reliable markers for estimating the degree of protein oxidation [2,5,19].…”
mentioning
confidence: 99%